Формування місцевих бюджетів в умовах реформування суспільних фінансів України - Катан, Людмила Ігорівна; Katan, Liudmyla; Качула, Світлана Валентинівна; Kachula, Svitlana; Демчук, Наталія Іванівна; Demchuk, Nataliia; Павлова, Діана; Pavlova, Diana (Дніпровський державний аграрно-економічний університет, 2020)
У статті розкрито соціально-економічну сутність, функції та роль місцевих бюджетів у системі суспільних фінансів України. Обґрунтовано, що в Україні сформовано достатньо розвинену систему формування доходів бюджетів, що охоплює відповідні складові, інститути та механізми, які все ще не повною мірою узгоджені між собою, відповідно недостатньо ефективно впливають на вирівнювання фіскальних дисбалансів розвитку адміністративно-територіальних одиниць. Здійснено оцінку доходів як основи формування місцевих бюджетів України та визначено вплив процесу реформування суспільних фінансів на розширення їх бази. Визначено роль міжбюджетних трансфертів у формуванні місцевих бюджетів України. Показано, що від якості планування доходів місцевих бюджетів значною мірою залежить ступінь ефективності здійснення органами місцевого самоврядування покладених на них функцій і повноважень, запланованих заходів, результативність бюджетної децентралізації. Окреслено заходи удосконалення системи формування місцевих бюджетів, що сприятимуть забезпеченню їх збалансованості та стійкості. The article describes the socio-economic nature, functions and role of local budgets in Ukraine's public finance system. It is substantiated that a sufficiently developed system of budget revenue generation has been formed in Ukraine, covering institutions and mechanisms that are not yet fully harmonized with each other. Accordingly, they have little effect on balancing the fiscal imbalances in the development of administrative and territorial units. The estimation of local budget revenues of Ukraine is carried out and the influence of the process of reforming public finances on the expansion of their base is determined. The role of intergovernmental transfers in the formation of local budgets of Ukraine is defined. It is shown that the degree of effectiveness of local self-government bodies implementation of the functions and powers assigned to them, the planned measures, and the effectiveness of budget decentralization largely depend on the quality of planning of local budget revenues. Measures to improve the system of formation of local budgets, which will help to ensure their balance and sustainability, are outlined. It includes the following: expanding the list of local budget revenues, improving the strategic and tactical planning system, taking into consideration the trends of exogenous and endogenous factors influencing the development of the system of local budgeting, optimizing inter-budgetary relations, stimulating entrepreneurship and creating new jobs, promoting incentives and job creation, informal employment. It is emphasized the need of increasing transparency and publicity in the decision-making process regarding the formation and use of budgetary funds, the publication of reports on the formation and implementation of budgets, the analytical evaluation of the effectiveness of local financial management, the financial performance of local governments. The feasibility of empowering local governments in terms of increasing sources of local budgeting is highlighted. At the same time, it is important to introduce and effectively implement the mechanism of financial control of local councils regarding the formation, distribution and spending of local budgets.
Local budgets formation in the conditions of reforming public finance of Ukraine
Keywords: місцевий бюджет; local budget; доходи місцевих бюджетів; local budget revenues; міжбюджетні трансферти; intergovernmental transfers; бюджетна децентралізація; budget decentralization; органи місцевого самоврядування; local governments